A high‐throughput and simultaneous determination of combretastatin A‐4 phosphate and its metabolites in human plasma using HPLC–MS/MS: Application to a clinical pharmacokinetic study. (6th July 2021) - Wu, Qizhen; Wang, Qian; Wang, Yixuan; Huang, Jingqiu; Fang, Yalin; Wu, Weiyi; Wu, Wenying; Wu, Fanhong; Yu, Xiaodong; Sun, Yan
Abstract: To investigate the clinical pharmacokinetics of CA4P, a high‐throughput high‐performance liquid chromatography–tandem mass spectrometry assay with an identical positive electrospray ionization (ESI) mode was developed for the simultaneous determination of CA4P, its active metabolite CA4, and CA4 glucuronide in human plasma. CA4P and CA4 were easier to protonate in positive ESI mode, whereas CA4G was reported to produce deprotonated ion in negative ESI mode. Because the baseline separation of CA4P and CA4G could not be achieved, using MS positive/negative ion switching is not feasible. In this study, an abundant ammonium adduct ion of CA4G in ESI+ was observed as an ideal precursor ion. The final precursor/product transition pairs chosen for CA4P, CA4, and CA4G were at m/z 397/350, 317/286, and 510/317, respectively. To the best of our knowledge, it is the first report on the simultaneous quantification of CA4P, CA4, and CA4G in biological samples. The proposed method was validated, which showed a wide linear dynamic range, high selectivity and sensitivity, good repeatability, and a short run time. Compared with the literatures, the lower limits of quantification were five‐ and two‐fold more sensitive for CA4G and CA4, respectively. Therefore, this method was successfully applied to the pharmacokinetic study of CA4P in phase I clinical trial.